Lyapunov estimation for high-speed demodulation in multifrequency atomic force microscopy - Harcombe, David M.; Ruppert, Michael G.; Ragazzon, Michael R. P.; Fleming, Andrew J. (Beilstein Journal of Nanotechnology, 2018)
An important issue in the emerging field of multifrequency atomic force microscopy (MF-AFM) is the accurate and fast demodulation of the cantilever-tip deflection signal. As this signal consists of multiple frequency components and noise processes, a lock-in amplifier is typically employed for its narrowband response. However, this demodulator suffers inherent bandwidth limitations as high-frequency mixing products must be filtered out and several must be operated in parallel. Many MF-AFM methods require amplitude and phase demodulation at multiple frequencies of interest, enabling both z-axis feedback and phase contrast imaging to be achieved. This article proposes a model-based multifrequency Lyapunov filter implemented on a field-programmable gate array (FPGA) for high-speed MF-AFM demodulation. System descriptions and simulations are verified by experimental results demonstrating high tracking bandwidths, strong off-mode rejection and minor sensitivity to cross-coupling effects. Additionally, a five-frequency system operating at 3.5 MHz is implemented for higher harmonic amplitude and phase imaging up to 1 MHz.
Keywords: atomic force microscopy (AFM); demodulation; digital signal processing; field-programmable gate array (FPGA); high-speed; Lyapunov filter; multifrequency